Divine Evolution: Empedocles’ Anthropology - A. V. Halapsis (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Reconstruction of Empedocles’ doctrine from the point of view of philosophical anthropology. Theoretical basis. Methodological basis of the article is the anthropological comprehending of Empedocles’ text fragments presented in the historical-philosophical context. Originality. Cognition of nature in Ancient Greece was far from the ideal of the objective knowledge formed in modern times, cognition of the world as it exists before man and independently of him. Whatever the ancient philosophers talked about, man was always in the center of their attention. I proposed an anthropological version of the interpretation of the doctrine of Empedocles, within the framework of which various elements of his concept fit into a consistent model. Conclusions. Empedocles’ anthropology is based on the recognition of several fundamental things. First of all, there is no death. Second, there is no fundamental difference between human and celestial. This line is conventional and under certain conditions one can overcome it. Cod can become a human (for example, for a deed unworthy of a deity), and a human can become God. Teaching of evolution is also double. Not only physical shell evolves, keeping only the most adapted species, but the soul too. The latter can both ascend to the gods and go down to the bushes and fish. Purification of the soul and mastering the magic of the elements gives an impetus for a correct direction of evolution. Empedocles is an anthropologist-practitioner, who shows by his example that a human can cope with all the elements and reach divinity. He chose (or convinced himself that he chose) the elemental ingredients for penetrating the Fortunate Isles, leaving the instructions on how to become God.